Shortcomings mentioned by the Torah about the prophet Lot in the prophecies and the respond of Quran - عبد الرزاق احمد عبد الرزاق نور هشام عبود (College of Education for Women, 2019)
Praise be to Allah , and peace and blessings of God sent mercy to the worlds Muhammad Amin and his family and his friends and followers to the Day of Judgement . Savants Jews worked to distort the Torah calamity on the Prophet Moses ( peace be upon him ) to achieve their goals and objectives , which are decorating sin to their followers , and spreading corruption on earth, through the charge prophets Bmvassad , morality, as the example and the example that emulate the human in the book of the Lord of the worlds and their Prophet Lot, described the weak, and cheese, and lack of modesty, and disobedience , drinking alcohol , and his failure to raise his two daughters , Jews are corrupt in the ground . Koran , which is the seal and dominated , and completely dominate that reveals many aspects of distortion and change that entered on the books , the Quran was and still trusted source of information is correct , which is not done wrong , however hands of his successor , revealing aspects of distortion and switches that have occurred on those books, including Torah Mazkrth for Prophet Lot ( peace and blessings be upon him ) of disadvantages , has absolved God from every gain of Torah to him, has necessitated the wisdom of the Almighty to be prophets fuller human beings created and created , and believe them in word , and the most proportions , and the very best note , and guided them nimble , Mbrin defects, because the prophets if they are not also small their business in the eyes of the people , and when he answered them one , so all the prophets lived all their lives infallible white page from fallinginto even become their sins after death lamps illuminate humanity through Rashad and Noor Hidayat . May Allah bless our Prophet Muhammad , his family , and his companions , much peace and recognition .